Prediction of Future Climate Change in Yangtze River Basin - WANG Chao; LI Hao; YE Xiuhui; RONG Qinbiao (Renmin Zhujiang)
Against the backdrop of global warming, the future climate of the Yangtze River Basin will undergo significant changes, and it is urgent to comprehensively evaluate the characteristics of future climate change in the Yangtze River Basin. This article analyzed the spatio-temporal variation characteristics of future temperature, rainfall, and runoff in the Yangtze River Basin based on observational data and global climate model prediction results, combined with the Mann-Kendall trend test method and land surface water balance budget method. The research has shown that with the continuous rise of greenhouse gases, the annual average temperature will rise by 0.23 °C/10a (SSP2-4.5) and 0.32 °C/10a (SSP5-8.5) from 2025 to 2100. Regions with elevated temperatures are mainly distributed in the southern part of the Yangtze River Basin. With the increase in the water vapor content in the atmosphere, the future rainfall in the Yangtze River Basin shows an increasing trend and increases significantly with the increase in radiation level. The increase in rainfall passes the 95% significance level of the Mann-Kendall trend test, and the annual increase is 1.32 mm/(month·10a) (SSP2-4.5) and 2.52 mm/(month·10a) (SSP5-8.5). The significant increase in rainfall in the Yangtze River Basin has led to an increasing trend of annual runoff in the future following the greenhouse gas concentration pathway, and the annual variation ranges are 1 371 m3/(s·10a) (Yichang Station), 827 m3/(s·10a) (Hankou Station), and 332 m3/(s·10a) (Datong Station), respectively, posing challenges for research on flood control, drought resistance, navigation, irrigation, and ecological water demand in the basin.